Predictors of digital competence of public university employees and the impact on innovative work behavior - Larissa Pinon de Carvalho; Thiago Poleto; Camila Carvalho Ramos; Fernando de Assis Rodrigues; Victor Diogho Heuer de Carvalho; Thyago Celso Cavalcante Nepomuceno (Administrative Sciences, 2023)
Digital competence plays an important role in higher education. The literature highlights the adoption and use of digital competence for the development of educational services in Higher Education Institutions (HEIs), but it is still necessary to understand its influence on the innovative behavior of the public official. This study aims to investigate the influence of digital competence, based on the predictors' infrastructure, integration, and digital management, on innovative work behaviors. The research was applied to 540 public employees of a Federal Institution of Higher Education (IFES) in northern Brazil. The response rate for this study was 33.5%. The Structural Equation Modeling approach by Partial Least Squares (PLS-SEM) was used. Empirical findings confirm that public employees with a high level of perception of digital competence more often develop challenging work to generate new innovative behaviors at work. This research was limited to investigating the influence of digital competence on innovative work behaviors of public employees of a Brazilian IFES. Future studies may address other contextual factors in this relationship. One of the practical implications is the need for managers in the education sector to support the construction of guidelines for educational and technological innovation to expand innovative behavior at work.
Keywords: 350; digital competence; education innovative; innovative work behavior; public administration